The pursuit of mathematical truths: a rich and meaningful aesthetic experience of inquiry - Ulliac, Kevin (My University, 2017)
Given a Deweyan philosophy of mathematics, education, and of the nature of experience, the pursuit of mathematical truths can be classified as rich and meaningful aesthetic experiences that are ends in themselves. My argument is that mathematical experiences of inquiry can have a meaningful impact on an individual that is of similar effect on an individual as a work of art, such as a painting, or a novel, or a piece of music. The nature of mathematical inquiry is to expand an individual’s conscious experience of themselves, their relation to other people, and their relation to the world at large.
Presented on April 24, 2017 at Student Research Day held at MacEwan University in Edmonton, Alberta.